Planning and development of sustanable logistics systems at a macro-level - Kovač Milovan G.; Tadić Snežana R.; Krstić Mladen D. (Tehnika, 2022)
The realization of a series of logistics activities, as support for goods flows, can result in serious negative consequences on sustainability if they are not planned properly. Road transportation's dominant role in existing logistics systems has serious unsustainable effects on the society and environment. The only way in achieving regional sustainability of logistics systems is in the utilization of alternative transportation modes through the application of intermodal transportation (IT). The planning of IT systems is a complex task that consists of determining the appropriate structure of the network, identification of efficient IT terminal types, their number, location, and role in the system, defining connections between terminals, etc. All that is preceded by the selection of the system development scenario. This article indicates the significance of IT in achieving sustainability at a macro-level. The Dry Port (DP) concept is highlighted as an instrument of achieving sustainable IT system development. Six potentially sustainable development directions of IT systems through the concept of DP are defined and explained.